Failure analysis on fully-transparent deep-sea pressure hulls used at 2,500 m depth - Wu, Yu; Li, Youjie; Luo, Ruilong; Zhang, Zhonggang; Wang, Fang; Zhao, Bingxiong; Yang, Chao; Zhang, Jinfei; Gaidai, Oleg (Frontiers in Materials, 2023)
Fully-transparent deep-sea pressure hulls have been attracted attention in recent years with the increasing demand for underwater observation. So far, public researches on design rule and failure modes for fully-transparent deep-sea pressure hulls are limited and the relevant experience cannot meet the requirements of new cabin design. Polymethylmethacrylate (PMMA) is the most commonly used transparent material. In this paper, based on the mechanical properties by compressive tests of PMMA samples, the finite element model is established in LS-DYNA software to conduct failure analysis of a typical fully-transparent deep-sea pressure hull after meshing sensitively study by comparing the simulated failure mode of specimen with test results. The first-order linear buckling modal analysis is carried out to simulate initial geometric imperfections before ultimate strength analysis under quasi-static external pressure. Simulation for the collapse process of fully-transparent pressure hull with two and one openings and ratio of thickness to radius t/R0 = 0.0685 are conducted for the present study. When the external pressure increases to 128 MPa and 126 MPa respectively, the two hulls begin to damage until they are completely broken. At the same time, simulation of sample pressure hull is carried out. The simulation results are compared with the experimental results in reference, which is basically consistent. The calculated failure strength shows that the spherical hulls satisfy the safety factor requirement of 5 times with their designed service depth of 2500m. The provided simulation procedure can be referred for failure analysis of fully-transparent pressure hulls.